Slovensko slovstvo v Istri pred prvo svetovno vojno - Košir, Diana (Slavistična revija, 2024)
The book collection of the monastery library of St. Ana’s is most accurately listed in the inventory book of the Library Collection Centre in Portorož (1950-1953). The monastery, which belonged to the Croatian province before World War I, also kept Slovenian prints in its library. The article provides an overview and textual description of the Slovenian works in the collection. The analysis revealed that the largest part of Slovenian print material was textbooks and technical manuals, liturgical and ascetic texts, and periodicals. Slovenian works indicate that some of the church rituals and devotions among the faithful, such as sermons, confession, religious instruction, preparation to receive the holy sacraments etc., were conducted by the Franciscans in Slovenian. An extensive range of secular, specialised didactic material and literature was provided for linguistic and general education. I conclude from this that the Slovenian book fund for Istrian monks and believers with Slavic roots also had a unifying and (by strengthening the language) nation-building function due to the linguistic element. The well-preserved and genre-diverse library collection of St. Ana’s is a valuable monument to prewar Slovenehood in a predominantly Romanesque urban environment. As far as the national collection of Slovenian and patriotic works is concerned, rare older and regionally coloured works are of particular interest.
Keywords: Fr. Hijacint Repič; Franciscans; frančiškani; knjižnica Sv. Ane; library of St. Ana; p. Hijacint Repič; Slovenian press; Slovenica; slovenika; slovenski tisk